(untitled) (Journal of the College of Basic Education, 2022)
The use of biodegradable nanoparticles as vaccine adjuvant with entrapped antigens represents an exciting approach for controlling the release of vaccine antigens and optimizing the desired immune response. Because of the natural components of nanoliposomes ,we investigated the ability of prepared nanoliposomes ,as a nanoadjuvant , to entrap soluble Leismania donovani antigens (SLAs) in order to be used in a vaccine against Leishmaniasis . In this study , parasite reactivation was carried out when inoculated into RPMI and incubated at 23 ̊ C for 4 days . L. donovani promastigote inoculum (104 cell / ml) of 4 days was used to inoculate modified medium of Saline - Neopeptone and Blood agar 9( SNB9) to produce promastigote mass . SLAs were extracted from the promastigotes ghost membrane after fourth passages of subculturing in SNB9 .The extracted SLAs then entrapped in nanoliposomes prepared freshly . Lipids mixture of 4mM Phosphatidylcholine, 2.2 mM Cholesterol and 0.55 mM Phosphatidylethanolamine in a ratio of 7:2:1 were used to prepare nanoliposome . Physio-chemical characterizations of prepared nanoliposomes was performed by using SEM , AFM and Zeta Potential assays to determine the size , morphology , chemical active group and charge . The efficiency of freshly prepared nanoliposoms to entrap SLAs was determined by measuring the nanoliposome efficiency entrapment (EE). The percentage of EE was 50 and 27.5of SLAs entrapped nanoliposomes prepared by Sephadex G25 and SephadexG75 , respectively .Moreover, stability of SLAs entrapped nanoliposomes was examined at 4 and 37 ̊ C storage temperature.